Face-to-Face Communication in Aphasia: The Influence of Conversation Partner Familiarity on a Collaborative Communication Task - Doedens, Willemijn; Bose, Arpita; Lambert, Lydia; Meteyard, Lotte (Frontiers in Communication, 2021)
Aphasia is language impairment due to acquired brain damage. It affects people's ability to communicate effectively in everyday life. Little is known about the influence of environmental factors on everyday communication for people with aphasia (PWA). It is generally assumed that for PWA speaking to a familiar person (i.e. with shared experiences and knowledge) is easier than speaking to a stranger (Howard, Swinburn, & Porter). This assumption is in line with existing psycholinguistic theories of common ground (Clark, 1996), but there is little empirical data to support this assumption. The current study investigated whether PWA benefit from conversation partner (CP) familiarity during goal-directed communication, and how this effect compared to a group of neurologically healthy controls (NHC). Sixteen PWA with mild to severe aphasia, sixteen matched NHC, plus self-selected familiar CPs participated. Pairs were videotaped while completing a collaborative communication task. Pairs faced identical Playmobile rooms: the view of the other's room was blocked. Listeners attempted to replicate the 5-item set-up in the instructor's room. Roles were swapped for each trial. For the unfamiliar condition, participants were paired with another participant's CP (PWA were matched with another PWA's CP based on their aphasia profile). The outcomes were canonical measures of communicative efficiency (i.e. accuracy, time to complete, etc.). Results showed different effects in response to the unfamiliar partner for PWA compared to NHC: In the instructor role, PWA showed faster trial times with the unfamiliar partner, but similar accuracy scores in both conditions. NHC, on the other hand, showed similar trial times across CPs, but higher accuracy scores with the unfamiliar partner. In the listener role, PWA showed a pattern more similar to NHC: equal trial times across conditions, and an improvement in accuracy scores with the unfamiliar partner. Results show that conversation partner familiarity significantly affected communication for PWA dyads on a familiar task, but not for NHC. This research highlights the importance of identifying factors that influence communication for PWA and understanding how this effect varies across aphasia profiles. This knowledge will ultimately inform our assessment and intervention of real-world communication.